Pergeseran Etika Tata Krama di Lingkungan Keluarga Suku Jawa Desa Mangga Dua Kec. Tanjung Beringin Kab. Serdang Bedagai - Parwati, Ria (UIN Sumatera Utara, 2023)
This research uses a qualitative approach because it seeks to provide a description of the influence of social layers and age in shifting and applying customary rules such as manners and rituals to the Javanese community in Mangga Dua Village. While this type of research is philosophical sociology because the object under study is the community group with the continuity of interaction in it, the existence of an applicable value system, and especially the deroutine of the old value system and social reproducibility through the recurrence of social practices. The study revealed that; 1) the ethical values of manners in the Javanese family environment consist of, namely; a) tolerance, (ethics of understanding), b) prioritizing the process of developing self-maturity, c) attitudes and choices are determined by the expectations of society, d) good and bad are relative, e) being subtle, f) being prudent. As for the ethics of manners, the most important thing is to be selfless which means accepting his own place, and fulfilling obligations which means doing what each human being should do according to his place in the cosmos. 2) the forms of shifting etiquette ethics in the Javanese family environment of Mangga Dua Village, Tanjung Beringin District, Serdang Bedagai Regency, are as follows; a) manners in communication: people have rarely used Javanese in interactions between individuals in their daily lives. In addition, in the family environment, communication between parents and children is dialogue or discussion, compared to the past which is listening and obedient. b) manners in social interactions: in this case there are still old values that continue to be maintained to this day are still in force, although the rules in this manners are not as strict as in the past. c) dressing: the Javanese people in Mangga Dua village only wear kebaya clothes during certain occasions.Keywords: Shift, Manners, Ritual.